(untitled) (Research, Society and Development, 2025)
Weight loss and weight control in combat sports (CS) expose athletes to periods of low energy availability (LEA), with potential physiological and psychological repercussions consistent with Relative Energy Deficiency in Sport (REDs). This article proposes a clinical–outpatient protocol to estimate energy availability (EA) and support screening/diagnosis of REDs risk in fighters of both sexes. The protocol integrates: (1) assessment of energy intake using standardized food records (with strategies to mitigate under-reporting); (2) estimation of exercise energy expenditure (EEE) via combat-sport-specific metabolic equivalents (METs), considering duration and body mass; and (3) determination of fat-free mass (FFM) using validated field methods (anthropometry and bioimpedance, with predictive equations). The proposed protocol aims to operationalize, outside the laboratory setting, systematic LEA screening and athlete monitoring across the off-camp, fight camp, and fight week phases, informing nutrition and training decisions that preserve health and performance. By standardizing feasible steps and tools, it contributes to primary prevention, early detection, and non-pharmacological management of Relative Energy Deficiency in Combat Sports (REDCS).